Women suicide bombers : narratives of violence - Rajan, V. G. Julie (Critical terrorism studies., 2011)
This book offers an evaluation of female suicide bombers through postcolonial, Third World, feminist, and human-rights framework, drawing on case studies from conflicts in Palestine, Sri Lanka, and Chechnya, among others. Women Suicide Bombers explores why cultural, media and political reports from various geographies present different information about and portraits of the same women suicide bombers.